Human and murine inhibitory natural killer cell receptors transfer from natural killer cells to target cells - Vanherberghen, Bruno (National Academy of Sciences, 2004)
Intercellular transfer of proteins across the immunological synapse is emerging as a common outcome of immune surveillance. We previously reported that target-cell MHC class I protein transfers onto natural killer (NK) cells expressing cognate killer Ig-like receptors (KIRs). We now show that, for both murine and human cells, target cells expressing inhibitory MHC class I ligands acquire cognate inhibitory NK receptors. Other cell-surface proteins, but not a cytoplasmic dye, also transferred from human NK cells to target cells across an inhibitory immunological synapse. The number of KIRs acquired from NK cells correlated with the level of expression of cognate MHC class I protein on target cells. Treatment with cytoskeletal inhibitors demonstrated that the target-cell cytoskeleton influences intercellular transfer of proteins in both directions. In contrast to constitutively expressed KIRs, a fraction of acquired KIRs could be removed by mild acid wash, demonstrating a difference between some of the acquired KIRs and constitutively expressed KIRs. An accumulation of phosphotyrosine at the location of the transferred KIRs implies a signaling capacity for NK cell proteins transferred to target cells. Thus, intercellular protein transfer between immune cells is bidirectional and could facilitate new aspects of immune cell communication.